2016
DOI: 10.1097/qai.0000000000001111
|View full text |Cite
|
Sign up to set email alerts
|

Topographies of Cortical and Subcortical Volume Loss in HIV and Aging in the cART Era

Abstract: Objectives Studies of HIV-associated brain atrophy often focus on a priori brain regions of interest, which can introduce bias. A data-driven, minimally-biased approach was used to analyze changes in brain volumetrics associated with HIV and their relationship to aging, viral factors, and combination antiretroviral therapy (cART), as well as gender and smoking. Design A cross-sectional study of 51 HIV-uninfected (HIV−) and 146 HIV-infected (HIV+) participants. Methods Structural MRI of participants was ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 114 publications
5
26
0
Order By: Relevance
“…A previous study conducting similar cross-sectional analysis confers HIV-infection in conjunction with aging is related to cortical volume loss. 48 Our findings of no cross-sectional differences by serostatus alone was unexpected, suggesting the uniqueness of this sample of long-term survivors, although, differences emerged when examining those with HAND compared to controls. Nevertheless, we note progressive atrophy despite minimal baseline cross-sectional findings and can conclude that these changes are not limited to those with past injury.…”
Section: Discussionmentioning
confidence: 56%
“…A previous study conducting similar cross-sectional analysis confers HIV-infection in conjunction with aging is related to cortical volume loss. 48 Our findings of no cross-sectional differences by serostatus alone was unexpected, suggesting the uniqueness of this sample of long-term survivors, although, differences emerged when examining those with HAND compared to controls. Nevertheless, we note progressive atrophy despite minimal baseline cross-sectional findings and can conclude that these changes are not limited to those with past injury.…”
Section: Discussionmentioning
confidence: 56%
“…In particular, CD4 nadir was positively associated with both global cortical area and volume, whereas duration of HIV infection was associated with smaller global cortical volume. Other groups have similarly reported that the severity of the initial immune compromise in HIV has long-term effects on brain area and volume, even when patients are adequately treated ( Guha et al, 2016 ; Hua et al, 2013 ; Sanford et al, 2017 ).…”
Section: Discussionmentioning
confidence: 96%
“…Structural MRI often reveals white matter changes of uncertain significance associated with HIV infection, but regional volumetric analysis can be a great tool to investigate progressive degeneration. [52] One of the very promising research imaging tools is PET scanning with ligands binding activated microglia that may be the effector cells for HAND. Early promising reports suggest this technology holds promise for HIV research.…”
Section: Brain Imaging and Handmentioning
confidence: 99%